INTERACTIVE BOOK DEVELOPMENT TO INCREASE STUDENTS’ UNDERSTANDING OF ‘MUSYAWARAH’ LEARNING MATERIALS AT CLASS III - Alivia Luthfansa Dhiaulhaq; Ani Nur Aeni; Aah Ahmad Syahid (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of students’ understanding of the PPkn learning subject, especially in the learning material of values of the 4th precept Pancasila, namely ‘Musyawarah’. The researcher found some problems related to the lack of innovation in the use of learning media so which causes students to have low interest in learning and to provide impact of students’ lack of understanding of the learning material. Using digital-based learning media, namely Interactive Books, is expected to be able to overcome the existing problem. The research method used is R&D with an approach of mixed method and the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). Research design uses One Group Pretest Design. The data collection techniques used are interviews and tests of understanding in the form of 15 questions of multiple-choice questions. The test is tested through SPSS software version 26 with the W-test (Wilcoxon) because the data research result in Posttest is not normally distributed. Measurement uses the N-gain test to measure and see how much percentage improvement before and after conducting treatment through learning media Interactive Book. Research results indicate that based on the testing, there is a change mark from Pretest to Posttest after conducting the treatment through i-book at 0.47 (47%) with medium criteria. It proves that Interactive Book produces an improvement or change to a better direction related to students’ understanding at class III SD of Panyingkiran II.